2019
DOI: 10.1021/acs.iecr.9b03565
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Escherichia coli-Based Cell-Free Expression Systems for Process Optimization

Abstract: Biotechnology has transformed the production of various chemicals and pharmaceuticals due to its efficient and selective processes, but it is inherently limited by its use of live cells as "biocatalysts."Cell-free expression (CFE) systems, which use a protein lysate isolated from whole cells, have the potential to overcome these challenges and broaden the scope of biomanufacturing. Implementation of CFE systems at scale will require determining clear markers of lysate activity and developing supplementation ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 31 publications
1
50
0
Order By: Relevance
“…In cases where increased yield is needed, there are some general approaches to further improve yield that we have yet to apply to this strain, such as: increasing the surface area to volume ratio, [56][57][58] implementing machine learning to improve reaction composition, 59 and conducting metabolomic studies to identify and optimize key metabolites. 60 However, even with these improvements, the SHuffle strain may continue to express less protein than other strains that are exogenously supplemented with T7RNAP and DsbC simply due to exhausted machinery. Yet, the facile, 'one-pot' approach presented in this work can still make a significant impact at the prototyping phase where a large amount of extract is needed to test many sequence candidates.…”
Section: Resultsmentioning
confidence: 99%
“…In cases where increased yield is needed, there are some general approaches to further improve yield that we have yet to apply to this strain, such as: increasing the surface area to volume ratio, [56][57][58] implementing machine learning to improve reaction composition, 59 and conducting metabolomic studies to identify and optimize key metabolites. 60 However, even with these improvements, the SHuffle strain may continue to express less protein than other strains that are exogenously supplemented with T7RNAP and DsbC simply due to exhausted machinery. Yet, the facile, 'one-pot' approach presented in this work can still make a significant impact at the prototyping phase where a large amount of extract is needed to test many sequence candidates.…”
Section: Resultsmentioning
confidence: 99%
“…While extremely useful as a standard across labs due to ease of measurement, the approach hides potentially large and complex underlying differences between methods [ 35 ], ignores the fraction of non-functional protein produced [ 151 ], and could poorly predict performance for some applications. The recent application of proteomics [ 112 , [152] , [153] , [154] ] and metabolomics [ 155 ] tools are important advances to better understand the underlying differences between extracts and CFE systems more generally.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is the precursor to pantothenic acid (vitamin B 5 ) and thus to Coenzyme A, an essential cofactor for many key metabolic pathways including the TCA cycle, fatty acid biosynthesis, and acetyl-CoA production 24,25 . Second, and perhaps even more noteworthy, we have previously shown that supplementing β -alanine to a CFE reaction increases protein expression 21 , indicating that its levels are (either directly or indirectly) important to CFE.…”
Section: Levels Of Multiple Key Metabolic Pathways Evolve Over the Course Of A Cfe Reactionmentioning
confidence: 96%